2010
DOI: 10.1016/j.autneu.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal motility disorders and acupuncture

Abstract: During the last decades, numerous studies have been performed to investigate the effects and mechanisms of acupuncture or electroacupuncture (EA) on gastrointestinal motility and patients with functional gastrointestinal diseases. A PubMed search was performed on this topic and all available studies published in English have been reviewed and evaluated. This review is organized based on the gastrointestinal organ (from the esophagus to the colon), components of gastrointestinal motility and the functional dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
120
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 80 publications
(98 reference statements)
1
120
1
Order By: Relevance
“…In contrast, some review studies were less conclusive regarding the effectiveness of acupuncture and acupressure for POI. Therefore, further valid and well-defined clinical studies are necessary to confirm the therapeutic effect of acupuncture and acupressure in POI treatment [10,15]. The purpose of this study was to find a noninvasive and costeffective treatment for POI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some review studies were less conclusive regarding the effectiveness of acupuncture and acupressure for POI. Therefore, further valid and well-defined clinical studies are necessary to confirm the therapeutic effect of acupuncture and acupressure in POI treatment [10,15]. The purpose of this study was to find a noninvasive and costeffective treatment for POI.…”
Section: Introductionmentioning
confidence: 99%
“…It is known as an effective treatment option for the management of postoperative nausea and vomiting, and various functional GI disorders [9,10]. Acupuncture is achieved by inserting the tips of thin, stainless steel needles on specific points (called acupoints) through the skin [10]. Conventional acupuncture involves the manipulation of the inserted needles by hand, such as lifting, thrusting, twisting, twirling, or other complex combinations [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EA has been demonstrated to modulate gastric motility through regulating the expression of transient receptor potential vanilloid 1, a Ca 2+ -permeable non-selective cation channel that has important physiological functions in peripheral and central nervous systems (20,21). In recent decades, numerous studies on patients and animals have been performed to elucidate the effects of acupuncture on gastric myoelectrical activity as well as the underlying mechanisms (4)(5)(6)(7)(8)(9)(10)(11)(12)(18)(19)(20)(21)(22)(23)(24). However, the exact mechanisms by which acupuncture improves gastric motility and dyspeptic symptoms have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Both animal experiments and clinical studies have shown that acupuncture can induce gastrointestinal transit after abdominal surgery and normalize gastrointestinal function [8][9][10][11]. Moreover, EA has been found to promote colonic motility and prevent formation of postoperative intra-abdominal adhesions [12,13].…”
Section: Introductionmentioning
confidence: 99%